Interleukin 10 protects primary melanocyte by activation of Stat-3 and PI3K/Akt/NF-κB signaling pathways. (July 2016) - Zhou, Jia; Ling, Jingjing; Song, Jing; Wang, Yong; Feng, Bainian; Ping, Fengfeng
Highlights: IL-10 had no direct effect on human primary melanocyte. IL-10 stimulation activated the JAK/Stat-3 and PI3K/Akt signaling pathways. IL-10 treatment caused increase translocation of p65 into nuclear compartment. IL-10 treatment up-regulated expression of Bcl-2 and Bcl-xL . IL-10 blocked cytochrome c release in H2 O2 -induced apoptosis. Abstract: Vitiligo is a common melanocytopenic disorder of the skin, with acquired focal depigmentation. Normal human skin relies on melanocytes to provide photoprotection and thermoregulation by producing melanin. Interleukin 10 (IL-10) is a pleiotropic immunoregulatory cytokine drawing more and more researchers' attention. The present study was conducted to investigate the effects of IL-10 on melanocytes and elucidate the underlying mechanisms. We proved that IL-10 play no role in regulating melanogenesis of normal human foreskin-derived epidermal melanocytes (NHEM). IL-10 stimulation activated the JAK/Stat-3 and PI3K/Akt signaling pathways. Moreover, IL-10 treatment increased translocation of p65 NF-κB into the nuclear compartment, and up-regulated expression of the pro-survival proteins Bcl-2 and Bcl-xL . IL-10 restored anti-apoptotic proteins expression and suppressed cytochrome c release in H2 O2 -induced apoptosis. In conclusion, IL-10 may provide pro-survival cues to melanocytes and be applied in the treatment of vitiligo and other depigmenting disorders.